2018
DOI: 10.1021/acs.jafc.8b02176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Treatment of Green Protein on in Situ Protein Disappearance and in Vitro Fatty Acid Biohydrogenation

Abstract: Soluble protein extracted from leaves and stems of grasses and forage legumes is defined as green protein. The present study was conducted to evaluate in situ green protein degradability, intestinal protein disappearance, and in vitro fatty acids biohydrogenation (BH) in dairy cows. Three green protein concentrates (red clover, ryegrass, and grass clover) were heat treated as follows: oven-drying at 70 °C, subsequent autoclaving at 121 °C for 45 min, and for grass clover also spin flash-drying. Freeze-dried gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 52 publications
2
8
0
1
Order By: Relevance
“…It is well established that free PUFA are more toxic than esterified PUFA to the function of rumen bacteria; therefore, the microbes biohydrogenate PUFA to avoid the toxic effect (Choi et al, ). In the present study, the V max and K M values of SA formation in different lipid fractions were unchanged, indicating that neither the decrease in substrate concentrations nor the accumulation of BH intermediates altered the SA formation (Chowdhury, Lashkari, Jensen, Ambye Jensen, & Weisbjerg, ).…”
Section: Discussionsupporting
confidence: 58%
“…It is well established that free PUFA are more toxic than esterified PUFA to the function of rumen bacteria; therefore, the microbes biohydrogenate PUFA to avoid the toxic effect (Choi et al, ). In the present study, the V max and K M values of SA formation in different lipid fractions were unchanged, indicating that neither the decrease in substrate concentrations nor the accumulation of BH intermediates altered the SA formation (Chowdhury, Lashkari, Jensen, Ambye Jensen, & Weisbjerg, ).…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, the applied heat in the present study did not overprotect CP and AA for small intestinal digestibility, and toasting of oat caused a shift in the site of AA digestion from the rumen to the small intestine. Chowdhury et al (2018) showed that Lys is one of the most heat-sensitive AA. Data on the Lys digestibility for diets with toasted oat were similar to the other treatments, which indicates that toasting oat at 121°C did not overprotect the CP.…”
Section: Digestion Of Cp and Aa In The Small Intestinementioning
confidence: 99%
“…The differences between green protein and soybean meal in the a and b fractions were balanced as the potential degradable fraction a + b was similar. Chowdhury et al (2018) also showed an increasing a fraction and decreasing b fraction in heat-dried green protein.…”
Section: Disappearancementioning
confidence: 84%